Analysis of the influence of organizational culture, training and compensation on the performance of education personnel (empirical study at the Faculty of Fisheries and Marine Sciences IPB) - Indupurnahayu, Renea Shinta Aminda; Awang Darmawan Putra; Amir Tengku Ramly; Niar Yuniarsih (Technium Social Sciences Journal, 2021)
Performing education personnel who does not meet the standards may affect a job assignment. High performance can improve the quality of a job, and efforts to improve performance continue to be carried out, one of which is by developing the existing organizational culture, conducting quality training, and adjusting to the provision of compensation, which may affect the performance of the Education Personnel. This study aims to analyze: 1) the effect of organizational culture on performance, 2) the effect on performance, 3) the effect of compensation on performance, and 4) the influence of organizational culture, training, and compensation on performance. The data collection technique used a questionnaire with a saturated sampling method where all population members (69 education personnel) were used as samples. Partial Least Square (PLS) based on Structural Equation Model (SEM) using SmartPLS 3.0 software used during data analysis. The results of the analysis show that: 1) organizational culture affects the performance of education personnel, 2) training affects the performance of education personnel, 3) compensation affects the performance of education personnel, and 4) organizational culture, training, and compensation together affect the performance of education personnel. Thus, the results indicate that organizational culture, training, and compensation do not have a positive and significant effect on the performance of education personnel at the Faculty of Fisheries and Marine Sciences, Bogor Agricultural University.